Method for simultaneous determination of three cooling agents in aerosols by GC–MS - Chen, Tinghao; Hua, Chenfeng; Ma, Chengjie; Peng, Bin; Shang, Pingping; Zhao, Ge; Yan, Quanping; Xie, Fuwei (Frontiers in Chemistry, 2025)
A cooling sensation is primarily elicited by cooling agents through activation of cold-sensitive receptors such as TRPM8 and TRPA1. Coolants are widely used as functional additives in various industries including food, personal care, pharmaceuticals, and tobacco. In this study, a gas chromatography–mass spectrometry (GC-MS) method was developed to quantify three representative cooling agents—menthol, WS-3(N-ethyl-2-(isopropyl)-5-methylcyclohexanecarboxamide), and WS-23 (2-Isopropyl-N,2,3-trimethylbutyramide)—in aerosol samples. The test aerosols were generated from laboratory-formulated e-liquids under optimized conditions. Aerosols were obtained from an electronic vaping device manufactured by RELX (China). The results demonstrated that: (1) the analytical method exhibited good linearity (R2 ≥ 0.9994), with limits of detection (LOD, from 0.137 ng/mL to 0.114 μg/mL), limits of quantification (LOQ, from 0.456 ng/mL to 0.380 μg/mL), relative standard deviations (RSDs, 1.40%–4.15%), and spiked recovery rates (from 91.32% to 113.25%) all meeting the requirements of analytical validation; (2) the cooling agents were detected in both gas and particle phases of the aerosol, with the concentrations in gas-phase being significantly lower than those in the particle phase due to aerosols condensation. Specifically, the gas-phase proportions of menthol, WS-23 and WS-3 ranged from 1.94% to 5.72%, 0.03%–0.08%, and 0.10%–0.18%, respectively. Therefore, the developed GC-MS method satisfies methodological validation criteria and is suitable for application to commercial aerosol samples. It provides a reliable analytical foundation for studying sensory perception of cooling agents under aerosol exposure and offers more precise guidance for their use.